ANALYSIS SERVICE QUALITY OF FRONT OFFICE DEPARTMENT AT HOTEL BALI MANDIRA RESORT & SPA - I Putu Edi Hendra Badrianta; Made Sudiarta; Ni Putu Somawati (Journal of Applied Sciences in Travel and Hospitality, 2019)
The purpose of this research is to examine the quality of service and to identify the service attributes which are well provided and the attributes that need improvement at the front office department at Hotel Bali Mandira Resort and Spa. The survey used 110 samples that were selected using incidental sampling. The analysis methods used are Servqual Analysis and Importance Performance Analysis (IPA) in the Cartesian diagram. The results of this research showed that the average value of ‘customer’s satisfaction’ which is expressed by ‘service performance’ is above 4 which is within the range value of 1 (least satisfy) and 5 (most satisfy). The Servqual analysis results show 9 attributes have slightly negative gap and 13 have positive gap; which show the quality of most attributes exceed customers’ expectation with some still below; nonetheless, the mean values of customer satisfaction for all variables are above 4. The results of the IPA analysis show, there are 2 attributes need improvement, the majority of attributes are well provided.